Women as American Family's health advocate, guide, or guardian: a health communication practitioners' perspective - Macias, Wendy (Frontiers in Communication, 2023)
American women are often in the role of being a health advocate, guide, or guardian for family and friends. An examination of gender differences is virtually absent from American-focused health communication literature. I review the topic from an international, professional, and historical perspective and include qualitative data from health communication professional interviews to document and explore this role. Explanatory themes of nature and nurture, as well as collectivism and having the ability to keep track of details, are explored as reasons why women take on these roles to a far greater degree than men. Suggestions for future research are included to encourage more health researchers to add to the academic literature.